Anatomy of the deep venous system in vein of Galen malformation and its changes after endovascular treatment depicted by magnetic resonance venography. (24th May 2018) - Winkler, Olivia; Brinjikji, Waleed; Lanfermann, Heinrich; Brassel, Friedhelm; Meila, Dan
Abstract : Background and purpose: It is classically thought that the internal cerebral veins (ICV) do not communicate with the venous pouch of vein of Galen malformations (VGM). We report on the anatomy of the deep venous system in VGM with special emphasis on the drainage of the ICV and possible changes after endovascular treatment. Materials and methods: We retrospectively analyzed DSA and 2D time-of-flight MR venograms of 55 children with VGM. We evaluated all pre- and post-operative images for the presence of the ICVs and determined their route of venous drainage. Results: Of 55 children, pre-operative 2D MRV detected the ICVs in 19 cases (35%) compared with one case (2%) for pre-embolization DSA (2%) (P<0.0001). Of the cases in which the ICVs were seen preoperatively, in 15 cases (78.9%) the ICV drained directly into the VGM while in the other four cases, the ICV used alternative venous drainage routes. On post-operative MRV, the ICVs were seen in 17 cases (31%) on MRV and 10 cases (18.2%) on DSA with drainage into an adult-like vein of Galen in 13 cases (76%), respectively (P=0.08). In four cases normal ICV drainage into the vein of Galen was seen even when the venous sac was closed. In two cases there was a change in ICV drainage from the vein of Galen to the lateral mesencephalic vein. Conclusion: The communication of the ICV with the VGM is a common phenomenon. Different changes of venous drainage routes do occur after treatment and are best seen on MRV.